2006
DOI: 10.1080/00365540500466614
|View full text |Cite
|
Sign up to set email alerts
|

Abducens nerve palsy and optic neuritis as initial manifestation in brucellosis

Abstract: Cranial nerve involvement in brucellosis is rare. We present a case of brucellosis presenting with optic neuritis and abducens nerve palsy on the left side. Cerebrospinal fluid findings indicated Brucella meningitis with high protein count, low sugar level and pleocystosis. In addition, Brucella agglutination test (Wright test) was found to be 1/128 in cerebrospinal fluid. Serum agglutination test for Brucella was also positive at 1/1280. This case was diagnosed as brucellosis involving optic and abducens nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…[7] Premacular hemorrhage detected in the right eye of our patient was considered to be related to an embolic process from the vegetation on the aortic valve. Cranial nerve involvement in neurobrucellosis has been reported previously,[8] however, neurobrucellosis and endocarditis complicated by premacular hemorrhage in our case from an endemic region was considered as a rare condition. Our patient showed dramatic clinical improvement after surgical removal of vegetation and replacement of aortic valve followed by specific treatment with rifampin and doxycycline for brucella.…”
Section: Discussionmentioning
confidence: 48%
“…[7] Premacular hemorrhage detected in the right eye of our patient was considered to be related to an embolic process from the vegetation on the aortic valve. Cranial nerve involvement in neurobrucellosis has been reported previously,[8] however, neurobrucellosis and endocarditis complicated by premacular hemorrhage in our case from an endemic region was considered as a rare condition. Our patient showed dramatic clinical improvement after surgical removal of vegetation and replacement of aortic valve followed by specific treatment with rifampin and doxycycline for brucella.…”
Section: Discussionmentioning
confidence: 48%
“…Neurobrucellosis manifesting as vasculitis, as seen in our patient, is an unusual but well-described manifestation of brucellosis [ 8 , 12 ]. While studies of patients with neurobrucellosis have shown the most commonly affected cranial nerve is VIII [ 1 , 10 ], and involvement of optic nerve secondary to vasculitis has been documented [ 10 , 15 , 18 ].…”
Section: Discussionmentioning
confidence: 94%
“…Choroiditis can also be induced by brucella, which is usually manifested as multifocal lesions or nodular or geographic changes ( 14 ). In addition, optic neuropathy has also been found in some brucella patients, which can be manifested as optic nipple hyperemia, retrobulbar optic neuritis, papilledema, and so on ( 15 ). Other manifestations of ocular brucellosis include endophthalmitis, lacrimal gland inflammation, episcleritis, keratitis, conjunctivitis, intracranial nerve palsy, and so on ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%